Odpowiedzi

Najlepsza Odpowiedź!
2009-11-21T17:47:18+01:00
A)(3+2√2)²= 9+12√2+8 =17+12√2
b) 3*(√5-4)²=3*(5-8√5+16)= 15-24√5+48=63-24√5
c) (3√3-2)²-(√3+1)²=27-12√3+4 - (3+2√3+1)=31-12√3-3-2√3-1=27-14√3
d) (√2+3) (√2-3)-(√2+3)²=2-9-(2+6√2+9)=-7-2-6√2-9=-18-6√2
e) (√5-3)²-2(√5-1)²=5-6√5+9-2(5-2√5+1)=14-6√5-10+4√5-2=2-2√5
2009-11-21T17:54:47+01:00
A)
9+12√2+8=17+12√2
b)
3*(5-8√2+16)=15-24√2+18=33+24√2
c)
(27-12√3+4)-(3+2√3+1)= 31-12√3-4+2√3=27-10√3
d)
(2-9)-(2+6√2+9)=-7-11+6√2=-18+6√2
e)
(5-6√5+9)-2(5-2√5+1)=(14-6√5)-(10-4√5+2)=14-6√5+9-12-4√5=
2-2√5